Health knowledge of adults in Polangui, Albay - Ante, Brenda Rosario 1948- ([place of publication not identified] [publisher not identified], 1974)
The health knowledge of adults in Polangui, Albay was determined in this study. Specifically, this research tested the extent of the health knowledge and the significant differences, if there are any, in the adults' health knowledge due to factors such as sex, age, marital status, occupation, income and educational attainment.
Typescript.
Thesis (M.Ed.)--University of the Philippines, Quezon City.
Keywords: Health education -- Philippines -- Albay